Impaired Vigilance Is Associated with Erectile Dysfunction in Patients with Sleep Apnea. (14th December 2014) - Popp, Roland; Kleemann, Yannick; Burger, Maximilian; Pfeifer, Michael; Arzt, Michael; Budweiser, Stephan
Abstract Introduction Erectile dysfunction (ED) is frequent in patients with obstructive sleep apnea (OSA) and may act as a surrogate of endothelial dysfunction. Furthermore, impairments of vigilance and sustained attention are also commonly associated with OSA. Aim The purpose of this study was to evaluate whether there is an association between ED and sustained attention deficits. Methods A prospective cross‐sectional cohort of 401 male in‐patients undergoing diagnostic polysomnography for suspected OSA and a 25‐minute sustained attention test was analyzed. ED was assessed using the 15‐item International Index of Erectile Function (IIEF‐15) questionnaire. The Epworth Sleepiness Scale (ESS) served as a measure of daytime sleepiness. Main Outcome Measure Severity of impaired erectile function (EF) assessed by the IIEF‐15, core task parameters of the sustained attention test (i.e., CR: correct reactions; V‐CR: variation of correct reactions, CE: commission errors, RT: reaction time; V‐RT: variation of reaction times). Results Three hundred eighty‐one consecutive patients presenting for in‐lab polysomnography were included in the analysis. Impaired EF was diagnosed in 246 patients (65%). With increasing impairment of EF, patients scored significantly worse in all vigilance test parameters and demonstrated more severely diminished vigilance (normal EF: 11.9%, moderately impaired EF: 24.1%, and severely impaired EF: 34.9%). Multivariate regression analyses including established risk factors for ED, OSA, or sleepiness revealed a significant independent association between lower scores for EF and impairments on the following vigilance test variables: odds ratio (95% confidence interval) for V‐CR: 0.52 (0.34–0.81), CE: 0.87 (0.80–0.95), and V‐RT: 0.91 (0.87–0.96). The ESS was independently associated with both measures of performance instability: odds ratio for V‐CR: 6.94 (2.97–16.23) and V‐RT: 1.28 (1.14–1.44). Conclusions In OSA patients, the severity of impaired EF was associated with impaired vigilance performance, independent of other known risk factors for ED or OSA and not mediated by sleepiness. Potentially, the findings suggest a direct relationship between vascular or endothelial dysfunction and impairments in both EF and neurobehavioral cognitive function. Popp R, Kleemann Y, Burger M, Pfeifer M, Arzt M, and Budweiser S. Impaired vigilance is associated with erectile dysfunction in patients with sleep apnea. J Sex Med 2015;12:405–415.